Marketing Efficiency of Enterprise Community of Preserved Chili - คงแก้ว, มัลลิกา; ฤทธิชัย, ทิพวรรณ (Ratchaphruek Journal, 2018)
The potentialities of marketing for community business at Tambon Khonhad, Amphur Cha uat, Nakhon Si Thammarat. The objectives of this research are to; 1) analyze marketing situation of processed chili, 2) increase the potential of marketing and 3) evaluate the potentiality of marketing. This study composed of three steps, and analyzed the marketing situation, developed marketing potential and evaluated the workshop reports and observations forms. The results of marketing situation for processed render three marketing strategies; 1) utilizing local raw materials to produced healthy products by using machinery, 2) emphasize quality of chili paste, which derived from local wisdom, and 3) direct sales to upper class healthy concerned customers. Two types of packaging were developed, which are bottle and sachet. The results of analyzing the cost of processed chili are as 1) sour soup chili paste is 39.625 Baht per 1 KG, 2) coconut milk chili paste is 51.625 Baht per 1 KG, 3) green curry chili paste is 51.625 Baht per 1 KG, 4) curry chili paste is 54.625 Baht per 1 KG, 5) Southern Dried curry chili paste is 44.625 Baht per 1 KG, and 6) Fish innards curry chili paste is 71.625 Baht per 1 KG. Increasing marketing channel via department store. The documentary was utilized as approach for marketing communication, which contained the process in producing chili paste, history and potential of community business group. The results of evaluating the marketing potential are as 1) the participants had high potential, 2) the marketing mix, which are products, price, place and marketing communication; were high level, and 3) sales and profits increased for 25 per cent.